2023
DOI: 10.3390/cancers15123140
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated microRNAs Involved in Prostate Cancer Aggressiveness and Treatment Resistance Mechanisms

Abstract: Prostate cancer (PCa) is the most frequently diagnosed cancer and the second leading cause of cancer deaths among American men. Complex genetic and epigenetic mechanisms are involved in the development and progression of PCa. MicroRNAs (miRNAs) are short noncoding RNAs that regulate protein expression at the post-transcriptional level by targeting mRNAs for degradation or inhibiting protein translation. In the past two decades, the field of miRNA research has rapidly expanded, and emerging evidence has reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 235 publications
0
3
0
Order By: Relevance
“…Epigenetics is also involved in regulating cell differentiation and development 48 . Differential expression of microRNAs is a critical epigenetic mechanism involved in the development and progression of human PC 49 . We previously demonstrated that miR-145, miR-148, and miR-185 were differentially expressed among patients with PC, PL and BPH 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics is also involved in regulating cell differentiation and development 48 . Differential expression of microRNAs is a critical epigenetic mechanism involved in the development and progression of human PC 49 . We previously demonstrated that miR-145, miR-148, and miR-185 were differentially expressed among patients with PC, PL and BPH 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The complete or partial pairing between miRNA and target mRNA, respectively, leads to the degradation or inhibition of protein translation genes. With this mechanism of action, miRNAs are involved in cell development, viral infection, immune response, angiogenesis, and the progression of many pathologies including breast, lung, colorectal, and prostate cancer [12][13][14][15].…”
Section: Mirnasmentioning
confidence: 99%
“…The genetic mechanism(s) that results in the loss of function of PTEN during the development of CRPC are not well understood. However, several miRNAs are involved in downregulating PTEN expression in PCa, suggesting that the deregulation of miRNA expression mediates the loss of PTEN function during PCa progression [60].…”
Section: Cell Signaling Molecules and Receptors: Pten Aurora Kinases ...mentioning
confidence: 99%